Assessing cardiac safety among clients receiving methadone as part of opioid agonist maintenance therapy (OAMT) in Durban, South Africa. Issue 1 (2nd January 2023) - Prakaschandra, Dorcas Rosaley; Scheibe, Andrew; Marks, Monique; Naidoo, Datshana Prakesh
Abstract: Background: : Methadone is a recommended medication for opioid agonist maintenance therapy (OAMT). However, methadone can have cardiac side effects. There is limited South African cardiac safety data on methadone. Objective: : To describe baseline and 12-month electrocardiographic (ECG) features and cardiac symptomology in people receiving OAMT in Durban, South Africa. Methods: : Twelve-lead ECGs were conducted at baseline and 12 months. Clinical interviews were used to assess cardiac symptomatology. Baseline ECG parameters (PR interval, QRS interval, QT and QTc duration, heart rate) were analyzed using descriptive statistics. Baseline and 12-month ECG characteristics were compared using paired T-tests in retained participants. The association between QTc and methadone dose was assessed using Spearman's Rho at 12 months. Results: : Fifty-three clients (51 men, 2 women [median age 29.0]) were initiated on OAMT. Normal baseline ECG variants included 4 (7.5%) with sinus bradycardia and 3 (5.7%) with ST segment elevation. Mean baseline ECG intervals were PR interval: 156 ± 23 ms, QRS duration: 87 ± 9 ms, QT interval: 404 ± 22 ms and QTc interval: 406.9 ± 21.9 ms. At 12 months, 39 participants returned for reassessment (mean methadone dose: 37 ± 8 mg in women; 27 ± 10 mg in men). QTc intervals among male participants increased (406.4 ± 22 to 417 ± 24; p = 0.026 [−19.6; −1.4]). No significant correlation ( r = 0.22; p = 0.185) between methadone dose and QTc interval at 12 months, nor reports of adverse cardiac symptomatology, were detected. Conclusion: : Methadone at the doses provided, caused mild and clinically insignificant QTc interval prolongation in men at 12 months. We provide additional cardiac safety data for the use of methadone for OAMT among people with opioid use disorder.